Variation in past tense marking in Bequia creole : apparent time change and dialect levelling - Daleszynska, Agata (The University of Edinburgh, 2012)
Research in the Caribbean often links global phenomena (e.g. increased tourism) to changes in lifestyles and mindsets taking place in this part of the world (Curtis, 2009). I examine the direction, intensity, and motivations of language changes among adolescents in three communities in Bequia (St. Vincent and the Grenadines) considering the socio-economic transformations affecting the island. Data for this study was obtained using a combination of sociolinguistic interviews and conversations between Bequia adolescents and their grandparents recorded in the course of several fieldwork trips. Three villages in Bequia were considered, Hamilton, Paget Farm and Mount Pleasant, characterised by different patterns of settlement and socioeconomic development. I investigate variation between: (i) creole verb stems vs. Standard English verb inflections (e.g. I go yesterday vs. I went yesterday), and (ii) verb stems and verb inflections vs. creole preverbal markers (e.g. I bin play yesterday). A variety of grammatical, discoursespecific, functional, and cognitive constraints are tested to determine which factors condition the variable patterns across different communities and age groups, and how linguistically similar/different these communities are. Results of the quantitative multivariate analysis of variation between bare verbs and inflected verbs show dialect levelling (Kerswill, 2003) among adolescents in Hamilton and Paget Farm and a transmission of the system (Labov, 2007) from the older generation to the younger in Mount Pleasant. In addition, adolescents in Paget Farm have recycled (Dubois and Horvath, 1999) a stigmatised creole form, preverbal bin, and are using it significantly more than any other group on the island. The study points to several important conclusions. Firstly, it emphasises the necessity for a multidisciplinary perspective in accounting for the factors which condition language change, especially in such a diverse and fast developing setting as the present-day Caribbean. Secondly, it supports the research on language and globalisation emphasising the relationship between the local and the global (e.g. Meyerhoff and Niedzielski, 2003). Finally, the study attempts to determine the nature of variation in creole languages as e.g. a creole continuum or co-existing systems, and establish replicable methods for measuring linguistic similarities/differences between communities.
Keywords: sociolinguistics; language change; Caribbean; creoles; identity; globalisation